A general approach for the characterization of fragmentation problems - Peukert, Wolfgang; Toneva, Petya Ivanova (Advanced Powder Technology, 2006)
A general approach for the quantitative and systematic characterization of fragmentation problems, which is based on the Weibull statistics, is presented. A model, initially developed for materials stressed under impact with respect to their breakage probability, has been successfully applied to the characterization of compressive comminution, fragmentation of nanoparticle agglomerates and destroying of adhesive bonds. The experimental results from the slow compression comminution and from the comminution by falling weight match for various materials and particle sizes exactly to the master curve deduced for impact comminution. However the material parameters determined for compression comminution are not identical for one and the same material to that determined by impact comminution. This indicates that the two model parameters are not pure material characteristics as assumed from the impact experiments but depend on the stress mechanism. The dependence of the fragmentation degree on the particle size and the energy input observed when impacting particles in the micrometer to millimetre range has been proven also for nanoparticle agglomerates. Furthermore a model analogical to that for breakage has been deduced for the quantification of the failure of adhesive bonds.
Keywords: Adhesion; Breakage probability; Fragmentation; Fragmentation degree; Modelling; Weibull statistics